Optimization of Microstructure and Mechanical Properties in Al-Zn-Mg-Cu Alloys Through Multiple Remelting and Heat Treatment Cycles - Peng Tang; Ronghui Pang; Hanbing Chen; Yulong Ren; Jun Tan (Metals)
This study explores the influence of multiple remelting and repeated T6 heat treatment on the microstructure and mechanical properties of Al-Zn-Mg-Cu alloys. With the increase in remelting cycles, the alloy experiences structural alterations due to recovery, recrystallization, and grain growth during remelting, which enhances its mechanical properties. However, the continuous transformation of alloy phases during remelting leads to the deterioration of the morphology and size of α-Al dendrites and MgZn2 phase, causing a decline in mechanical properties. The results indicate that after three remelting cycles, the grain size of the alloy is significantly reduced, and the α-Al dendrites and MgZn2 phase maintain favorable morphology and size, thereby achieving the effects of grain refinement and strength enhancement. These findings offer a theoretical foundation for optimizing the properties of Al-Zn-Mg-Cu alloys.